An Analysis on Runaway from Perspective of Cognitive Dissonance - Wang, Ting (Pacific International Journal, 2022)
The short story Runaway is one of the same name collection.Carla eloped with her boyfriend Clark when she was 18 and cut the contact with family. After experiencing the suffering from the marriage, she started the second escape but gave up in the end. Cognitive Dissonance refers to a situation involving conflicting attitudes, beliefs or behaviors. Carla, the protagonist experienced the ignorance to the point of unbearable. When she almost closed to the new life, she gave up with the influence of Cognitive Dissonance. This paper analyzes essential reasons of the two escapes of Carla in Alice Munro's short story Runaway from the perspective of Cognitive Dissonance. Strategies of dissonance relieving are offered for middle-aged woman who suffered from the mind dissonance.